Doprinos Matije Murka proučavanjima južnoslovenske epike - Buturović, Đenana (Traditiones (Ljubljana), 1999)
Slovene Slavicist and ethnologist Matija Murko (1861-1951) has dedicated a large part of his professional endeavours to the epic poetry of South Slavs. The author discusses ˝Tragom srpsko-hrvatske narodne epike˝ (On the Trail of Serbo-Croatian Folk Epic Poetry, published in 1951), Murko,s fundamental work, analyzing especially Murko,s view of the Moslem epis poetry
Keywords: Murko, Matija, 1861-1952; Ethnopoetics; ljudske pesmi; slovstvena folklora; Južni Slovani